Persuasive Illocutionary Speech Acts in Canva Advertisements on the Ptalform: A Linguistic Approach - Lathiva Istavida; Joko Wibowo (English Lecturers and Teachers Association (ELTA), 2026)
This study aims to analyze the types and functions of illocutionary speech acts used in Canva digital advertisements and their role in persuasive communication. The data consist of verbal texts extracted from 15 Canva advertisements published in June 2025. Using a qualitative descriptive approach grounded in Searle’s speech act theory, this study examines assertive, commissive, directive, and expressive speech acts. The findings reveal that commissive speech acts dominate Canva advertisements, emphasizing promises and commitments to users, followed by assertive acts that enhance credibility. Expressive and directive acts appear less frequently, indicating a preference for soft persuasion strategies that maintain user autonomy. Data reveals commissive speech acts dominate Canva's approach at 89%, primarily through commitments to user empowerment and creative support. Assertives follow at 67%, establishing credibility through factual claims about design capabilities and platform accessibility. Expressives appear in 33% of cases, often reinforcing user confidence through value affirmations. Notably, directives remain minimal at 22%, suggesting strategic avoidance of overt persuasion tactics that might compromise perceived user autonomy. Practical recommendations include enhancing expressive elements during onboarding sequences where user anxiety peaks, embedding verifiable data within assertive claims about design outcomes, and refining commissive language for clearer expectation management regarding platform capabilities. Keywords : Illocutionary Speech Acts; Digital Advertising Discourse; Pragmatics; Persuasive Language; Canva Advertisements